2009
DOI: 10.1177/1470320309343813
|View full text |Cite
|
Sign up to set email alerts
|

Association of angiotensin-converting enzyme intron 16 insertion/deletion polymorphism with history of foetal loss

Abstract: Introduction. The angiotensin-converting enzyme (ACE) intron 16 insertion/deletion (I/D) polymorphism is associated with ACE activity and has been discussed as a risk factor for pre-eclampsia. Disturbances of uteroplacental circulation are involved in the pathogenesis of pre-eclampsia. In this study, we tested whether the ACE I/D genotype is associated with history of foetal loss (FL) or uteroplacental dysfunction (UPD). Patients and methods. ACE I/D genotype was determined in 312 women presenting with a histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 18 publications
3
17
0
Order By: Relevance
“…Our results are supported by the findings of Vettriselvi et al., Goodman et al., Al Sallout et al., Bagheri et al., and Aarabi et al., but our results are not supported by others (Fatini et al., Buchholz et al., Bukreeva et al., Corbo et al., Zhang et al., Ozdemir et al.) . An association between the ethnicity of the study population and the genetic contribution to the etiology of venous thromboembolism is possible, and ACE I/D has been found to be significantly associated with VTE, especially in African‐American populations .…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Our results are supported by the findings of Vettriselvi et al., Goodman et al., Al Sallout et al., Bagheri et al., and Aarabi et al., but our results are not supported by others (Fatini et al., Buchholz et al., Bukreeva et al., Corbo et al., Zhang et al., Ozdemir et al.) . An association between the ethnicity of the study population and the genetic contribution to the etiology of venous thromboembolism is possible, and ACE I/D has been found to be significantly associated with VTE, especially in African‐American populations .…”
Section: Discussionsupporting
confidence: 49%
“…The I/D polymorphism accounted for 47% of the phenotypic variance of serum ACE concentration, and the variant D/D genotype was associated with a high circulating ACE level; thus, the D allele of the ACE gene might be associated with increased levels of PAI‐1 . Given this, the ACE gene I/D polymorphism has also been investigated in connection with RPL, and these studies have yielded diverse results . Recently, three meta‐analyses reported a significant association between the ACE I/D polymorphism and idiopathic RPL .…”
Section: Introductionmentioning
confidence: 99%
“…There were some significant evidences showing that the RAS had taken part in the onset of some renal diseases [9], [10], [11], [12]. The level of plasma ACE, constitutively expressed in several types of somatic cells, is linked to an I/D polymorphism of 287 bp in intron 16 of the ACE gene [35], [36], [37]. D allele and DD homozygous have been reported to be associated with higher plasma ACE level [6], [16].…”
Section: Discussionmentioning
confidence: 99%
“…15 relevant studies were identified that described the association between the ACE I/D polymorphism and RPL. While reading the full texts, the following articles were removed: two studies did not meet Hardy-Weinberg equilibrium (P 0 0.0003 and P 0 0.0217, respectively) [25,26]; one study could not extract the allele data (ACE I/D in RPL) from its groups [27]; one study was not only focused on RPL, but also on pre-eclampsia and foetal growth restriction which made it hard to get the data required [28]; and the other two studies included the data of case and control groups, but little information about the ACE I/D polymorphism [16,29]. Finally, there were 9 studies meeting the inclusion criteria that were included [11,[30][31][32][33][34][35][36][37].…”
Section: Characteristicsmentioning
confidence: 99%